Respuesta del cultivo de col (Brassica olerácea) a la aplicación de tres tipos de abonadura orgánica en la zona de Otavalo, provincia de Imbabura - Rea Betancourt, Fausto Danilo (2012)
The present investigation was carried out in the properties of the School "Carlos Ubidia Albuja" of the Parish Miguel Egas Heads, belonging to the Canton Otavalo, County of Imbabura, with coordinated geographical 0º 19' 28 '' of north latitude, 78º 07' 53 '' west of south longitude and to an altitude of 2.600 msnm. It was used as genetic material, the seed of cabbage variety "Gloria". The treatments were constituted by the doses of organic abonadura with the help of worm Humus, Gallinaza and Bovinaza, in dose of 8000, 12000 and 16000 kg/ha, more the absolute witness. The design experimental Complete Blocks was used at random (DBCA) with ten treatments and three repetitions. All the variables were subjected to the test of Multiple Ranges of Duncan. They were carried out all the necessary agricultural works in the cultivation for their normal development, as preparation of the nursery, preparation of the floor, abonadura, transplant, resiembra, watering, control fitosanitario, fertilization, control of overgrowths and it harvests. To estimate the effects of the treatments they took the following data: prendimiento percentage, height of the plant, days to the crop, diameter of the pellet, weight of the pellet, yield and economic analysis.......